PENGARUH KEPEMIMPINAN DAN BEBAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KANTOR SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KOTA SIBOLGA - Telaumbanua, Antonius Khouwa’auri; Sipahutar, Hadijah; Lubis, Rifka Hadia (Lembaga Pengembangan Kinerja Dosen, 2023)
In general, this study aims to determine the influence of Leadership and Workload on Employee Work Effectiveness at the Secretariat Office of the Regional People's Representative Council of Sibolga City. The type of research used in this research is descriptive correlational research, which describes and provides an explanation of the relationship between variable X (independent) as the independent variable that influences and variable Y (dependent) as the dependent variable that is influenced. For this study, the population was only Civil Servants consisting of 10 Structural Officials and 29 Staff at the Secretariat Office of the Regional People's Representative Council of Sibolga City, totaling 39 (thirty nine) Civil Servants. The analytical method used is the efficiency analysis technique of multiple correlation and multiple linear regression. The results showed that based on statistical testing partially showed t count 3.641 > t table 0.208 and a significant value of 0.001 <0.05, it means that the Leadership variable partially has a positive and significant effect on the Work Effectiveness variable. The workload variable shows t count 0.448 > t table 0.208 and a significant 0.004 <0.05, it means that the workload variable partially has a positive and significant effect on the work effectiveness variable.